Optimasi Proses Ekstraksi Propolis dari Limbah Perasan Madu Trigona dengan Penggunaan Pelarut Air - Tri Isti Rahayu; Sinaga, Yesica Marcelina Romauli; Perdhana, Firman Fajar; Zuhdia, Lulu Diani (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Propolis is a natural resin produced by bees and has various health benefits that have been extensively studied. The extraction of propolis from Trigona honey pass residues generally uses organic solvent. Propolis can be extracted using water as a solvent with certain treatments. The study aims to obtain an optimal propolis extraction using a water solvent which is known to be safe and cheap. The optimization process of water extraction was combined with various extraction methods such as cold maceration, hot maceration (temperature 60°C), Ultrasound-Assisted Extraction (UAE), and Microwave-Assisted Extraction (MAE), compared to organic solvent controls and commercial propolis. The parameters observed from the obtained extracts are pH, phytochemical screening (alkaloids, phenolics, saponins, steroids, and flavonoids), color, antioxidant activity, and antibacterial activity. The data was analyzed using analysis of variance with the level of significance set at 5%. The results showed that the water extraction with MAE produced propolis extract with the highest antioxidant content and performed bacterial growth inhibition against Escherichia coli and Staphylococcus aureus.